An unexpected hotspot of moth biodiversity in Chilean northern Patagonia (Lepidoptera, Geometridae) - Hausmann, Axel; Parra, Luis E. (Zootaxa, 2009)
In a small area around Huinay station, northern Patagonia (Chile), 75 geometrid moth species were collected at light in three subsequent nights, 87 in a short 11-day period under suboptimal weather conditions. This surprisingly high diversity is due to lack of habitat destruction and complete overlap of Valdivian and Patagonian fauna elements. An annotated neighbour joining tree of COI data (5’ barcoding fragment) is presented and the taxonomy of all species is discussed. Three new combinations are proposed: Danielaparra fragmentata (Dognin, 1906), comb. n., transferred from Hoplosauris; Hoplosauris multivirgulata (Mabille, 1885), comb. n., transferred from Physoloba; Calta debilis (Butler, 1882), comb. n., transferred from Odontothera. Daniela viridis (Parra, 1996) is a new synonym of Danielaparra fragmentata.